Comparative evaluation of prevalence and phenotypic variations of Candida species in patients of oral lichen planus and oral lichenoid lesions with healthy individuals - A prospective microbiological study - Sarkate, Priyadarshani; Pathak, Jigna; Patel, Shilpa; Swain, Niharika; Sahu, Nikita (Journal of oral and maxillofacial pathology : JOMFP, 2022)
Context: Candida isolates might exaggerate the development and advancement of oral lichen planus (OLP) alone or together with other factors. There is a differing pathogenic potential of various Candida species. Since Candida species isolated from OLP and oral lichenoid lesions (OLL) have shown to be resistant to commonly used antifungal agents, identification of Candida species may play a pivotal role in its successful clinical management. Aim: The aim of the study was to evaluate and compare the prevalence and phenotypic variations of Candida species in patients of OLP and OLL with healthy controls. Subjects and Methods: This prospective microbiological study was conducted in the institution using indirect microscopic examination. The sample comprised of 40 clinicohistopathologically diagnosed cases of the study group (OLP and OLL) and 40 cases of control group (healthy individuals). Statistical Analysis Used: The data collected was statistically analyzed using the Chi-square test and Fisher's exact test with the SPSS 20.00 software. Results: The prevalence of Candida albicans was higher in the control group (28.10%) as compared to the study group (24.60%) and this difference was statistically significant. An increased frequency of non C. albicans species was seen in the study group, in decreasing order of Candida glabrata (40.70%), Candida tropicalis (22.20%), Candida krusei (22.20%) and Candida guilliermondii (3.70%), as compared to the control group. Conclusion: Non C. albicans species were the predominant pathogens associated with the study (OLP + OLL) group. It is important to identify the infecting strains of Candida because isolates of Candida species differ widely, both in their ability to cause infection and also in their susceptibility of resistance to antifungal agents. Thus, phenotypic speciation of Candida is emerging as a necessary trend to highlight the need of administering appropriate antifungal therapy.